The Impact of the Russian-Ukrainian War on the Global Economy - Sasidharan, Revathy Githa (Journal of Global Economy, Business and Finance, 2024)
The most unexpected thing happened just as the globe was beginning to recover from the COVID - 19 pandemic and there was hope for the economy to be rebuilt. The Russian invasion of Ukraine on February 24, 2022, was seen by the entire globe. The day of the invasion saw a decline in stock values. Not just the economy of Russia and Ukraine suffered during the initial months of the invasion, many other nations also suffered greatly because of the conflict. Food prices increased dramatically worldwide because of the conflict between these two nations. The cost of food increased as well as there was an increase in the price of crude oil. Thus, resulting in Global inflation. Numerous European nations placed harsh sanctions on Russia to lessen the impact of the conflict. However, this did not create much of an impact since These sanctions had a serious impact on both the European nations and the nations that were not involved in the conflict. This resulted in a serious inflation issue that affected both combatant and noncombatant nations worldwide. This paper focuses on the global economic effect of the Russia and Ukraine war and how the actions of one country can create a serious impact on the globe.